Analysis of the Medical Record Document Maintenance System in the Filing Room of the Health Center Sei. Asam: Analisis Sistem Pemeliharaan Dokumen Rekam Medis Di Ruang Filing Puskesmas Sei. Asam - intannia, dwininda (Sekretariat Program Studi Sarjana Terapan Manajemen Informasi Kesehatan Politeknik Indonusa Surakarta., 2022)
Sei Asam Health Center in the medical record document storage room is poorly maintained because there is no temperature control to maintain humidity, there are medical record documents stored in cardboard or on the floor and there is still dust in the medical record documents and in the storage room. This can risk the medical record document to be damaged. The purpose of this research is to analyze the medical record document maintenance system in the filing room of the Sei Asam Public Health Center. This research uses a qualitative research type. The input has material components and storage space which has been checked by the filing and registration officer. Get the corrupted and uncorrupted files, the damaged files are divided into corrupt, unmaintainable and damaged, can be preserved. files that cannot be preserved (damaged/unreadable) are carried out unplanned maintenance by destruction. While files that can still be preserved (readable) and files that are not damaged are carried out by planned maintenance by performing routine maintenance of files that produce useful files.